Improving performance of emergency escape ramps (EERs). Issue 4 (3rd April 2022) - Besiktepe, Deniz; Valdes-Vasquez, Rodolfo; Strong, Kelly; Shuler, Scott
Abstract: Highway downgrades for heavy trucks generate a potential safety risk and disruption for truck drivers and other road users. Emergency escape ramps (EER) are the standard method of accommodating runaway trucks in the downgrade sections of highways. The aging EER infrastructure, along with the increasing number of truck incidents in mountainous highways, creates the need for research into best practices for improving the performance of EERs. The research approach of this study consists of a multi-methods design, including a review of the literature, appraisal of incident reports from a mountain state DOT during the last decade, field observations and aggregate analysis at four EERs along a heavily transited mountain interstate, and evaluation of interstate stakeholder perceptions via focus group, surveys, and interviews. The product of this research is a series of recommendations to improve EER performance, operations, and maintenance practices. These practices can help sustain a highway system, which effectively and safely moves people and freight.